Determinan Nilai Perusahaan Kunci Keberlanjutan: Kontribusi Karbon, Green Intellectual Capital, dan Media Exposure - Vanisa Ratna Sari; Umi Hanifah; Erna Chotidjah Suhatmi (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study analyses the impact of carbon emission disclosure, carbon performance, green intellectual capital, and media exposure on firm value in the energy sector. Environmental damage triggered by industrial activities and increased greenhouse gas concetrations have pushed companies to be transparent and responsible for their carbon footpint. This study uses a quantitative approach with secondary data from annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange from 2021-2024 using a purposive sampling technique. Panel data regression analysis with the Random Effect Model was applied to test the hypotheses. The test result show that carbon emission disclosure, carbon performance, and green intellectual capital affect firm value. Media exposure does not affect firm value, indicating that investor do not use media exposure as a primary signal.